2017
DOI: 10.3892/ijo.2017.4023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a-5p enhances cisplatin-induced apoptosis in ovarian cancer cells by targeting multiple anti-apoptotic genes

Abstract: MicroRNAs play a crucial role in gene expression regulation in various types of cancers. Previous studies show the expression level of miR‑146a‑5p is downregulated in epithelial ovarian cancer. Further investigations suggest this downregulation is responsible for apoptosis resistance in ovarian cancer cells. However, the mechanism of how miR‑146a‑5p promotes apoptosis remains unclear. In this study, the role of miR‑146a‑5p in cisplatin‑induced apoptosis of ovarian cancer cells was assessed by DAPI staining, MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Cisplatin is one of the most effective chemotherapy drugs, the underlying mechanism of cisplatin resistance has been studied for decades; however, there are no effective pharmacological operations to overcome this form of complex resistance (29)(30)(31). It has been widely reported that miRNAs regulate cisplatin resistance in various cancers (31)(32)(33)(34)(35), but has rarely been reported in RCC. Recently, miR-126 targeting SERPINE1 (36) and miR-148a targeting Rab14 (37) were identified to regulate cisplatin-resistance in RCC, and it was also reported that miR-124 represses FZD5 to attenuate P-glycoprotein-mediated doxorubicinand vinblastine-resistance in RCC (38).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is one of the most effective chemotherapy drugs, the underlying mechanism of cisplatin resistance has been studied for decades; however, there are no effective pharmacological operations to overcome this form of complex resistance (29)(30)(31). It has been widely reported that miRNAs regulate cisplatin resistance in various cancers (31)(32)(33)(34)(35), but has rarely been reported in RCC. Recently, miR-126 targeting SERPINE1 (36) and miR-148a targeting Rab14 (37) were identified to regulate cisplatin-resistance in RCC, and it was also reported that miR-124 represses FZD5 to attenuate P-glycoprotein-mediated doxorubicinand vinblastine-resistance in RCC (38).…”
Section: Discussionmentioning
confidence: 99%
“…Vera et al (37) demonstrated that DNA methylation of miR-7 participated in the OVC DDP resistance through MAF bZIP transcription factor G (MAFG); Yu et al (33) reported the mediation of DDP resistance in OVC by miR-21 by targeting PTEN. Additionally, Li et al (38) demonstrated that miR-146a-5p facilitated OVC DDP resistance by suppressing several antiapoptotic genes, including baculoviral IAP repeat containing (BIRC), BIRC2, BCL2L2 and X-linked inhibitor of apoptosis. Overexpression of miR-139-5p can reverse DDP resistance in OVC by targeting C-Jun (39).…”
Section: Discussionmentioning
confidence: 99%
“…There was a converse association between the levels of miR-142-5p and XIAP expressions in OC patients [ 23 ]. MiR-146a-5p also induced DDP-mediated apoptosis by XIAP, BCL2L2, and BIRC5 targeting in OC cells [ 24 ]. It has been reported that miR-509-3p , miR-519d , miR-155 , and miR-130a promoted DDP mediated apoptosis through XIAP targeting in OC cells [ 25 28 ].…”
Section: Main Textmentioning
confidence: 99%
“… Li [ 23 ] 2019 miR-142-5p China XIAP 19 patients SKOV3 and OVCAR3 cell lines Increased DDP sensitivity. Li [ 24 ] 2017 miR-146a-5p China XIAP, BCL2L2, and BIRC5 OVCAR3 and SKOV3 cell lines Increased DDP sensitivity. Chen [ 25 ] 2016 miR-509-3p China XIAP SKOV3 and A2780 cell lines Increased DDP sensitivity.…”
Section: Introductionmentioning
confidence: 99%